Over a million students use our free study notes to help them with their homework
This question is about rearranging the equation so that all the known variables are on one side and all the unknown variables are on the other side. To start with we can look at the x terms, remembering t...
A student will often see the equation of a circle in the form (x-a)2+(y-b)2=r2. In this instance, a and b simply represent numbers. They are not variables. In fact, a repr...
To solve an algebraic equation you need to rearrange it into the format x=? To do this there are a few rules and few steps
Rules:
wh...
Firstly, begin by multiplying both sides of the equation by (x-2) and (x+3), this gives 6(x+3)-2(x-2)=(x+3)(x-2). Expand out the brackets on each side of the equation to give 6x+18-2x+4=x2-2x+3...
(1) x2 + 15x + 56 = 0
56 = 1 x 56, 2 x 26, 4 x 14, 7 x 8
7 + 8 = 15
Hence, factorised equation is (x + 7)(x + 8) = 0
←
644
645
646
647
648
→
Internet Safety
Payment Security
Cyber
Essentials